Science Learning Strategy Based on Ethno-Socioscientific Issues (ESsI): Analysis of Creative Thinking Ability in Students' Science Reconstruction - Ahmad Khoiri,; Budiyono Saputro,; Bambang Parikesied,; Mohd Fauzi Sedon,; Nasokah, (Jurnal Pendidikan IPA Indonesia, 2026)
This study aims to map science reconstruction, determine the profile of creative thinking skills, and assess the effectiveness of high school science learning strategies based on the ESsI approach. The research method is a mixed-method explanatory sequential design. The purposive sampling technique is based on the distance from the school location to the district center (City, Middle, and Village) in Wonosobo and Boyolali Regencies. The quantitative analysis techniques are normality and homogeneity testing, the t-test, and ANOVA, and the qualitative analysis is inductive-deductive. The results of the highest level of reconstruction in the PS (Potential Scientist Student) category of SMA C (village) are that students easily understand cultural traditions as science. The highest IDKS (I-do-not-know student) category is in SMA A (City), where students find it difficult to understand their own traditions and culture. In the highest OS (Outsider) category in SMA C (village), students find it very difficult to recognize and understand traditions and culture, so they are unable to understand science as a whole. While in the IOS (Inside Outsider) category, none of the schools are at the lowest level. The creative thinking skills profile of SMA B (middle) is the highest among SMA A (City) and SMA C (Village). This shows that all high schools that use the ESsI strategy for learning can empower creative thinking skills. The contribution of students' science reconstruction research is very important, particularly in light of cultural background, to determine freedom of thought based on life habits.